Medical treatment of ADHD : a practical guide for clinicians, counselors, and parents - Odell, J. Dennis (John Dennis) (New York, NY : Routledge, 2021)
This practical and easily navigable book covers the gamut of issues that need to be understood to provide excellent medical care for those with ADHD. Outside of mental health professionals, those who most often treat ADHD are primary care providers such as family practitioners, pediatricians, nurse practitioners, physician assistants, and school personnel. Based on clinical conversations with patients with ADHD and their families, this book provides concise, useful, up to date information of a practical nature for most, if not all of the problems, associated conditions and questions that arise when an individual has concerns about ADHD. Treatments discussed include a thorough review of medication options, with expected results and side effects, as well as other recommended treatments including a variety of therapeutic modalities, and a review of less commonly considered but important interventions regarding general health, sleep, diet, exercise, and school interventions. Readers will gain an understanding of what ADHD is, practical reviews of the literature that will help in discussion with patients and their families the importance of intervention, and all the resources and options available to provide the best treatment strategies for anyone who has ADHD as well as the commonly associated conditions.
Introduction : An Overview of ADHD -- Historical Perspective -- Consequences of ADHD -- ADHD-Predominantly Inattentive Presentation -- Learning Disabilities -- Disruptive Behavior Disorders -- Anxiety, Mood Disorders and ADHD -- Autism and ADHD -- Other Symptoms and Conditions Associated with ADHD -- Assessment / J. Dennis Odell MD and Martin Toohill Ph.D -- Medication Management -- Medication for Conditions Associated with ADHD / J. Dennis Odell MD and George Wootton FNP -- Behavior Therapies / J. Dennis Odell MD and Camille Odell MS -- Other Interventions for ADHD.
OCLC-licensed vendor bibliographic record.
Keywords: Attention-deficit-disordered children; Attention-deficit disorder in adolescence; Attention-deficit hyperactivity disorder; PSYCHOLOGY / Psychopathology / Attention-Deficit Disorder (ADD-ADHD)